2010
DOI: 10.1016/j.diamond.2010.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Local boron doping quantification in homoepitaxial diamond structures

Abstract: The capability of transmission electron microscopy (TEM) using the high angle annular dark field mode (HAADF, also labelled Z-contrast) to quantify boron concentration, in the high doping range between 10 19 cm − 3 and 10 21 cm − 3 , is demonstrated. Thanks to the large relative variation of atomic number Z between carbon and boron, doping concentration maps and profiles are obtained with a nanometer-scale resolution. A novel numerical simulation procedure allows the boron concentration quantification and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…VTEM techniques for high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) have been shown to be so accurate as to replace the need for experimental calibration standards in compositional analysis [13]. Through VTEM, contrast features due to the environment, detector angles, specimen thickness, specimen orientation, defocus, aberrations, structural strain, interfaces, and composition have been determined [1425]. As recent studies have demonstrated lattice fringe observations during in situ liquid experiments performed under BF-TEM or HAADF-STEM imaging modes [1, 26, 27], VTEM can provide insight into such high resolution contrast features observed in situ .…”
Section: Introductionmentioning
confidence: 99%
“…VTEM techniques for high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) have been shown to be so accurate as to replace the need for experimental calibration standards in compositional analysis [13]. Through VTEM, contrast features due to the environment, detector angles, specimen thickness, specimen orientation, defocus, aberrations, structural strain, interfaces, and composition have been determined [1425]. As recent studies have demonstrated lattice fringe observations during in situ liquid experiments performed under BF-TEM or HAADF-STEM imaging modes [1, 26, 27], VTEM can provide insight into such high resolution contrast features observed in situ .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows the experimental and simulated HAADF intensities, with very good agreement between them. Details of how simulations are carried out have been published elsewhere [9]. As can z (nm) 80nm…”
Section: Reflexion Dfmentioning
confidence: 99%
“…Lett. 103, 042104 (2013) in SIMS measurements, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] leading to systematic overestimates of the real width, similar to the case of silicon. 26 If this is the case, it is legitimate to ask how the layer thickness should be estimated from broadened SIMS profiles.…”
Section: -3mentioning
confidence: 99%
“…The need of an imaging method able to quantify boron content and layer thickness becomes obvious when d-doped devices are being developed. For this reason, high angle annular dark field (HAADF 17 or Z-contrast mode) using a STEM (scanning transmission electron microscope) to thin homoepitaxial multilayers in order to determine the thickness, interface sharpness, and boron content of these doped structures is here applied. Recently, boron doping was also observed using this technique on nanocrystalline diamond.…”
mentioning
confidence: 99%
See 1 more Smart Citation